Critical Analysis of Moral Decadence in Darul Arafat High School Bumi Ratu Nuban, Central Lampung Regency - Marzuki, Lukman; Hidayat, Febri (Episteme: Jurnal Kajian Mahasiswa, 2025)
Moral decadence among students has become an alarming phenomenon that affects educational institutions, including SMA Darul Arafah Bumi Ratu Nuban, Lampung Tengah. This study aims to critically analyze the forms, causes, and potential resolutions of moral decline among high school students through a qualitative phenomenological approach. Data were collected through interviews, observations, and documentation involving teachers and students. The findings reveal that the main contributing factors to moral decadence include negative peer influence, excessive exposure to social media, lack of parental supervision, and limited understanding of religious and ethical values. Observable behaviors indicating moral decline include truancy, smoking, classroom misconduct, verbal abuse, and disinterest in learning activities. As a response, the school implements corrective strategies such as verbal reprimands, counseling, and behavior-based discipline. The study offers a novel contribution by emphasizing the integration of value-based character education and culturally relevant pedagogical approaches as sustainable solutions to rebuild student morality. These findings provide practical implications for educators, parents, and policymakers in shaping student character within religious and moral frameworks.